Transverse basilar cleft: Two more probable familial cases in an archaeological context. (6th August 2018) - Tur, Svetlana Semenovna; Svyatko, Svetlana Vladimirovna; Rykun, Marina Petrovna
Abstract: Transverse basilar cleft (TBC) is a very rare congenital anomaly representing a coronal fissure completely or partially intersecting the basioccipital at the level of the pharyngeal tubercle. It is usually asymptomatic but can sometimes be part of a syndrome. Population frequencies of this anomaly are no more than 1%, with few exceptions. Two skulls with TBC were found in the Ayrydash 1 cemetery of Altai Mountains nomads, Russia, attributed to the Hunno‐Sarmatian period (2nd c. BC–5th c. AD). In this paper, we test the possibility of a familial relationship between the individuals who shared by this condition, using the Alt and Vach method for nonspatial analysis of skeletal kinship based on cranial and dental nonmetric traits. Results of the study show that the frequency of TBC is significantly higher in the Ayrydash 1 sample than in the rest of the skeletal population from the Hunno‐Sarmatian period ( p  < 0.05). This suggests that the individuals affected by TBC were most likely genetic relatives. The observed clustering of TBC and some other rare anomalies within local groups of Altai Mountains nomads appears to be due to parental consanguinity in their community.